Exercise Motivation and Affective Experiences of Recreational Runners in Central Finland - Merkulov, Kirill (2024)
In developed, high-income countries like Finland, the changing trends in technology promote the physical inactivity among people in all age groups, which leads to the embracement of sedentary lifestyles, especially in winter. Specifically, employment that allows working on computer or from a home, screen-based leisure time activities (video games, movies) and transportation. There is solid evidence that regular engagement in physical activity (PA) is essential to maintain and promote physical and psychological health. There has been little attention in literature on the psychology of recreational runners. To address this gap in literature, the first goal of this thesis was to explore the difference in motivation for physical activity between gender. The second goal was to research the affective experiences of recreational runners before and after marathon participation. The results of research on motivation and affective experiences of recreational runners can be used to design motivating PA intervention to facilitate peoples’ PA and well-being. The participants of this study were from the Finlandia 2023 marathon in Jyväskylä, Finland. The data about the motivation was collected using the Physical Activity and Leisure Motivation Scale (PALMS). The affective states were collected using the Affective Exercise Experiences (AFFEXX) questionnaire. Results revealed significant differences between males and females in exercise participation motives, particularly in competition/ego and others’ expectations. Results also revealed no significant changes in AFFEXX scores pre and post marathon. This study showed there is a difference in motives to exercise between gender and this can lead to developing unique interventions for people. Specifically, the results suggest specialists should consider having an open-minded approach when creating PA interventions for their clients based off intrinsic and extrinsic motives. Lastly, this study offers an opportunity in future research to examine if a balance between the two motivators (intrinsic and extrinsic) can have the best impact on maintaining a lifelong physical activity habit and creating an active and balanced lifestyle.